The Effectiveness of Aromatherapy on Depression Among Senior Citizens Residing in Selected Old Age Homes in Satara District - Pawar, Pratibha; Pawar, Shivaji; Potdar, Nutan; Rajsinh Mohite, Vaishali (Journal of Neonatal Surgery, 2025)
Introduction: Depression is a common mental health disorder marked by pervasive feelings of sadness, isolation, irritation, diminished self-esteem, despair, restlessness, and guilt, frequently accompanied by physical symptoms. Aromatherapy, a complementary medicine practice, utilizes plant materials and aromatic oils to influence mood, cognition, psychological state, and physical well-being. Neroli oil, a favored option in aromatherapy, is esteemed for its lovely aroma and possible therapeutic benefits. Materials and Methods: A quantitative approach with a one-group pretest-posttest design, was conducted in selected old-age homes. The target population includes senior citizens residing in these facilities. The sample consists of 60 individuals aged 60 and above, selected through purposive sampling, all diagnosed with depression. Discussion: Aromatherapy significantly reduced depression levels among senior citizens in old-age homes (P < 0.0001). However, socio-demographic factors did not demonstrate a notable connection with levels of depression in this group. The mean depression score decreased significantly from 27.18 ± 5.58 to 22.33 ± 5.00 (t = 15.704, p < 0.0001) after aromatherapy. There is no association between pre-test levels of depression with demographic variables among senior citizens. Result: The study assessed the level of depression in senior citizens before and after aromatherapy. In the pretest, most participants (73.34%) experienced moderate, (21.67%) had severe, (3.33%) mild, and (1.66%) had borderline clinical depression. Post-test results revealed that the majority (53.33%) had borderline clinical, (40%) had moderate, (3.34%) had normal, and (3.33%) still had severe depression. The mean depression score decreased significantly after aromatherapy, indicating a substantial reduction in depression levels following the treatment. Conclusion: In conclusion, aromatherapy is shown to be effective in lowering depression levels among elderly individuals living in retirement homes.